Resource Allocation: Managing Money and People - Norton, M. Scott; Kelly, Larry K. (The school leadership library, 1997)
This book shows you how your school can maintain its high standards despite financial obstacles. It shows you how to investigate various types and sources of money available to your school; monitor the use of scarce school resources; develop a school improvement plan which incorporates financial needs; and recruit, assign, and develop teachers and staff for maximum effectiveness.